Strategic Decision-Making of Elementary School Principals in Implementing Deep Learning-Based Independent Curriculum - Nuri Ria Sri Wahyuni; Eka Putra (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to describe the principal's decision-making strategy at SDN 020/XI Koto Lebu, Pondok Tinggi District, Sungai Penuh City, in supporting effective school management and improving teacher performance, particularly in the implementation of the deep learning-based Independent Curriculum. The study employed a qualitative approach with a case study method. Data collection techniques included in-depth interviews, non-participant observation, and documentation studies, with key informants being the principal, teachers, and education staff. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the principal's decision-making strategy was carried out systematically, participatory, and data-driven, through the stages of problem identification, information collection and analysis, deliberation with the school community, and continuous evaluation of the policies taken. This approach reflects the optimal implementation of the principal's managerial functions, including planning, organizing, implementing, and supervising. An open and accountable decision-making strategy has been shown to have a positive impact on improving teacher performance, creating harmonious cooperation, and successfully implementing the deep learning-based Independent Curriculum. This study confirms that the principal's decision-making is a strategic factor in improving the quality of school management and the quality of learning in public elementary schools.